Modulation indices embedded carrier-based PWM generation for modular multilevel converter - Tohtayong, Majdee; Khan, Sheroz; Yaacob, Mashkuri; Mohamud Ahmed, Musse; Yusoff, Siti Hajar; Midi, Nur Shahida (2018)
The fundamental component (50Hz) in the output voltage of a single-phase modular multilevel converter (MMC) can be diverted by varying of the value of modulation index (Mi). However, this changing affects on the value of the total harmonic distortion of the output voltage (THDv) and output current (THDi). Moreover, the variableness of modulation index can be differentiated to be linear region and over-modulation region to consider the correlation of modulation indices and fundamental component, and THD. Each region has a different effect on THDv and THDi. To facilitate, this paper demonstrations the results of carrier-based PWM strategy simulation in a singlephase 7-level MMC with a single-phase induction motor as a load to study the behavior of THDv and THDi when the modulation index value is changed.